The Dynamic Association of Interest and Confusion: The Potential for Moderation by Utility Value and Gender. Issue 3 (1st May 2020) - Geerling, Danielle; Butner, Jonathan; Fraughton, Tamra; Sinclair, Sungchoon; Zachary, Joseph; Sansone, Carol
Abstract: To better understand students' experiences while learning in an online computer-science course, we adopted a dynamical systems analytic framework in which we tested linked patterns of confusion and interest over time and investigated whether and how those patterns might change as a function of students' exposure to a utility value (UV) intervention and gender. We assessed interest and confusion via event contingent experience-sampled questionnaires that displayed immediately after students had engaged with key examples or exercises. Results indicated that students' exposure to a UV intervention and gender affected the levels of confusion that students reported and the associations between interest and confusion levels over time. Implications for educators and researchers are discussed.